Breaking down walls in prostate cancer with the MURAL collection of patient-derived xenografts - Charlotte L. Bevan (Nature Portfolio, 2021)
A bank of 59 well-characterised prostate cancer patient-derived xenografts was established, including 17 classed as research-ready covering the disease-spectrum which, plus associated resources (organoids, serum, DNA/RNA profiles, tissue), are available for collaborative projects. This eagerly-anticipated resource will facilitate pre-clinical prostate cancer therapy studies.